2008
DOI: 10.1645/ge-1411.1
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium Infection Causes Undernutrition and, Conversely, Weanling Undernutrition Intensifies Infection

Abstract: Cryptosporidium parvum is a leading pathogen in children in developing countries. To investigate whether early postnatal malnutrition leads to heavier C. parvum infections, we assessed intestinal adaptation and parasite load in suckling mice during the first 2 wk of life, analogous to the first postnatal yr in humans. Undernutrition was induced by daily C57BL6J pup separation from lactating dams. Half of the pups were separated daily, for 4 hr on day 4, 8 hr on day 5, and for 12 hr from day 6 until day 14. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 51 publications
3
65
1
Order By: Relevance
“…Although growth failure was present in nourished mice, the effect was modest and delayed relative to the more profound decrement seen in the setting of malnutrition. Counter to other enteric infections in malnutrition (32)(33)(34), this compounded effect cannot be explained by a higher burden of infection in the malnourished mice. Intriguingly, another investigation also demonstrated a relatively decreased burden of G. lamblia trophozoites in the small bowel following severe PD in mice (44).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although growth failure was present in nourished mice, the effect was modest and delayed relative to the more profound decrement seen in the setting of malnutrition. Counter to other enteric infections in malnutrition (32)(33)(34), this compounded effect cannot be explained by a higher burden of infection in the malnourished mice. Intriguingly, another investigation also demonstrated a relatively decreased burden of G. lamblia trophozoites in the small bowel following severe PD in mice (44).…”
Section: Discussionmentioning
confidence: 93%
“…More recently, Shukla et al showed growth impairment in BALB/c mice infected with axenic trophozoites, although infection did not worsen the growth impact of PD compared with controls (30). We have previously demonstrated that malnutrition using a low-protein (LP) diet worsens growth after infection with enteroaggregative E. coli and Cryptosporidium in both neonatal and weaned murine models (31)(32)(33)(34). We have seen from these studies that malnutrition leads to heavier infection and increased proinflammatory signaling, while infection leads to further weight faltering, thus replicating a "vicious cycle" of malnutrition and intestinal infection (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…The cryptosporidial colonization of the small and large intestine results in destruction of enterocytes. Contrary to isolated bacterial or viral infections, mixed infections with C. parvum are associated with shortening of intestinal villi and persistent severe disorders of digestion and absorption (Coutinho et al 2008, Ok et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…While the diarrhea of neonatal calves is usually associated with bacterial (E. coli) or rotaviruses and coronaviruses infections, Cryptosporidium spp. seems to be the most common cause of diarrhea in older, 3-week-old animals (Coutinho et al 2008, Foster and Smith 2009, Ok et al 2009). Clinical signs of diarrhea include loose watery stools, lack of appetite and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and animal studies suggest a role between infection and inflammation causing deranged immune signaling leading to enteropathy and poor growth [17][18][19]. These models, which need further validation in human studies, demonstrate that specific nutrient deprivation has a profound impact on the character and intensity of inflammation [19,20], such as an apparent bias away from Th1-type primary immune responses (Bartelt, unpublished) similar to what has been shown in malnourished children in Haiti with cryptosporidiosis [21].…”
Section: Introductionmentioning
confidence: 90%